Formulation and comparative evaluation of allopurinol transdermal patches using two different polymeric combinations - Adity Modak; Tiyash Roy; Abhishek Jana; Swarnim Gupta; Pintu De (Creative Pharma Assent, 2026)
Background: The transdermal drug delivery system is a technique where drugs are absorbed via the skin at a predetermined and controlled rate. This system offers several benefits over conventional routes, such as intravenous or oral administration, for both systemic and local drug delivery, and it is simple to administer. This technique is also painless. The goal of the dosage model for transdermal medications is to simultaneously enhance drug efflux from the skin into the systemic circulation while minimizing drug metabolism and retention in the skin. The selected drug for the present formulation is Allopurinol, a xanthine oxidase inhibitor that lowers uric acid levels in the body. Methodology: The goal of this study is the development of a matrix-type transdermal system of allopurinol with two different hydrophilic polymers, polyethylene glycol-4000(PEG-4000) and hydroxyl propyl methyl cellulose (HPMC), along with a hydrophobic polymer, Ethyl cellulose (EC), in different ratios by using the solvent evaporation technique to create a suitable matrix-type patch. Results and Discussion: The physicochemical characterization of thickness, folding endurance, moisture content, and drug-polymer compatibility has been studied. The drug release studies from the formulation, P1F3, showed maximum release of allopurinol (59.43%) in 5 h, where EC: PEG-4000 was 2:1; whereas P2F3 showed maximum release of allopurinol (57.28%) in 5 hours, where EC: HPMC was 2:1. In both cases, the release rate is retarding by increasing the proportion of hydrophobic polymer EC. Conclusion: The physicochemical evaluation of the prepared transdermal patches revealed good physical stability, with controlled drug release achieved by varying the ratios of hydrophilic and hydrophobic polymers.